Effects of artificial diets on lipid and glucose metabolism, antioxidative capacity, and inflammation in the liver of mandarin fish (Siniperca chuatsi) - Fang, Wei; Leng, Xiangjun; Yun, Biao; Wang, Lei; Qian, Xueqiao (Frontiers in Marine Science, 2024)
The mandarin fish (Siniperca chuatsi) is a typical carnivorous fish, which has been able to consume artificial diets after domestication in recent years. However, the potential health consequences of artificial diets in mandarin fish remain unclear. This study aimed to elucidate the molecular mechanisms underlying these concerns. Fish (initial weight: 25.1 ± 0.1 g) were fed with natural (CON group) or artificial diets (AF group) for 8 weeks. Each diet was randomly distributed to sextuplicate circular tanks (300 L) with 40 fish in each tank. The transcriptome analysis revealed significant changes in metabolism-related pathways, particularly those involved in lipid and carbohydrate metabolism. Further investigation confirmed that the artificial diets significantly increased hepatic triglyceride content and fatty acid synthase activity. The artificial diets also significantly increased hepatic glycogen and glucose-6-phosphatase activity. Furthermore, the artificial diets significantly increased hepatic malondialdehyde levels, indicating increased oxidative stress. Antioxidant defense enzyme activities and the expression of antioxidant stress-related genes were significantly decreased. Additionally, the artificial diets significantly increased the expression of proinflammatory genes, including interleukin 1 beta and interferon-gamma. These findings collectively demonstrated that the artificial diets disrupted hepatic lipid and glucose metabolism, leading to oxidative stress and inflammation, thus affecting the health status of mandarin fish.